In-Service Teachers views and conceptions on culture and mathematics education in rural schools. - Muzangwa, Jonatan; Chindanya, Dr.Andrew (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The teaching of culture and heritage studies is the flagship of Great Zimbabwe University. This present study is investigating preliminary views and conceptions of in-service teachers on culture and mathematics education. Data was collected through a questionnaire survey on all 27 teachers who majored in mathematics education. The group was considered small enough to render sampling unnecessary. It was observed that a good part of students were aware of the significance of the role of culture on mathematics education whilst some were not very sure how culture played a role in the field of mathematics. We recommend the school curriculum to implement culture-oriented mathematics education that ensures the survival of African culture.